Tipologi Pola Asuh dalam Al-Qur’an: Studi Komparatif Islam dan Barat - Izzatur Rusuli (Fakultas Ushuluddin, Adab dan Humaniora (FUAH) UIN Kiai Haji Achmad Siddiq Jember, 2020)
Abstract: Parenting is the way parents behave, interact and treat their children. This paper aims to examine the family concept and typology of parenting from the perspective of the Qur'an and its comparison with Western parenting styles. This research is a literature review by tracing the verses of the Qur'an related to parenting. The results of this study indicate that the concept of family in the perspective of the Qur'an is based on parents' understanding of family goals. Meanwhile, from a Western perspective, parenting is influenced by external conditions of the family. The typology of parenting in the perspective of the Qur'an is determined from the goal of raising a family, saving the family from hellfire, and maintaining the nature of the child from birth. From these two goals, parenting styles in the Qur'an can be mapped into two, they are caring and ignorant parenting. Meanwhile, the typology of parenting in a Western perspective refers to two dimensions; responsiveness and demandingness resulting in four types of parenting; authoritative/democratic, authoritarian, permissive, and neglectful styles. The aim of Islamic parenting is not only for achieving happiness and family harmony in the world but also in the hereafter. Meanwhile, the aim of Western parenting is only to achieve happiness and family harmony in the world.